Anticipating and designing for policy effectiveness. Issue 1 (2nd January 2019) - Bali, Azad Singh; Capano, Giliberto; Ramesh, M.
ABSTRACT: The new design orientation in the policy sciences has placed renewed emphasis on problem-solving and developing effective public policies. In this paper, we contribute to this scholarship by presenting a policy framework on anticipating effective policies. We argue that anticipation – that is, foreseeing the future and preparing for it – must be central to how a policy is designed, executed and assessed. Anticipating policy effectiveness requires a careful understanding of the problem and its root causes, as well as selection and utilization of the most 'appropriate' policy instrument(s) to solve it. We consider 'appropriateness' along three dimensions – analytical, political and operational – in two different respects: choice of policy tools and the capacity of the implementing agency.